Madrasah Aliyah Curriculum Management In Improving The Quality Of Islamic Religious Education (Pai) Learning : (Case Study of MAN 2 Pulang Pisau and MA Darul Ulum Palangka Raya City) - Iim Wasliman, Supyan Sauri, Ricky Yoseptry, Amruddin, (Design Engineering, 2024)
Many educational institutions have implemented curriculum management, but most need help with the implementation stage. Curriculum management aims to ensure that the curriculum prepared is effective and efficient in achieving the educational goals that have been set. With good curriculum management, academic institutions can provide relevant and practical education to students. This research aims to analyze planning, organizing, implementing, evaluating and curriculum management solutions to improve Islamic religious education (PAI) learning quality at MAN 2 Pulang Pisau and MA Darul Ulum, Palangka Raya City. This research uses a case study method with a qualitative approach through observation techniques, interviews and documentation studies. This research found that (1) Curriculum planning was carried out involving various parties and referred to the Indonesian Ministry of Religion regulations. (2) The organization of the curriculum has been carried out based on the Decree of the Head of the Madrasah as a result of deliberations regarding teacher workload instructions and MA-level curriculum organization. (3). The curriculum implementation is carried out based on the direction and explanation of the MA level PAI curriculum implementation. (4) Evaluation of the PAI curriculum in improving the quality of PAI learning is carried out normatively, including summative and formative assessments, improving the quality of PAI learning. (5) The problem of curriculum management in improving PAI learning is still faced with the problem of teacher resources that are less than proportional in the division of work, and (6) Solutions to overcome curriculum management problems in improving the curriculum can be done with curriculum management that focuses more on achieving the quality of PAI learning.